MULTIPLE ENVIRONMENTAL AND SOCIAL DETERMINANTS OF HEALTH FACTORS WERE NOT ASSOCIATED WITH THE GASTROINTESTINAL SYMPTOMATIC BURDEN OF ULCERATIVE COLITIS WITH MUCOSAL HEALING. (26th January 2023) - Tse, Chung Sang; Yonan, Aed; Nguyen, Hang; Dulai, Parambir; Singh, Siddharth; Dervieux, Thierry; Gaidos, Jill; Valasek, Mark; Neill, Jennifer; Le, Helen; Collins, Angelina; Boland, Brigid
Abstract: INTRODUCTION: In a biopsychosocial interdisciplinary model, complex interactions between the hosts (individuals/patients), disease (e.g., ulcerative colitis [UC]), and environment (e.g., social determinants of health [SDOH]) may all contribute to the disease burden. Whether SDOH contributes to the symptomatic burden of UC in deep remission is unclear. METHODS: We performed a secondary analysis on prospectively collected data from adults with UC enrolled in the biobank at a tertiary referral center in southern California from 2014-2021. Standardized clinical (unweighted two-item patient-reported outcome [PRO-2] for stool frequency [SF] and rectal bleeding [RB]; remission=SF0/RB0), endoscopic (Ulcerative Colitis Endoscopic Index of Severity [UCEIS]; remission UCEIS=0), and histologic (Geboes score; remission <2B.0) disease activity assessments were performed within 30 days of a colonoscopy (case) with segmental colonic biopsies. SDOH were assessed using the California Healthy Places Index (SDOH Index), a publicly available zip code-based system that ranks SDOH domain and subdomain scores from the least to most healthy (0-100 percentile) using weighted z-scores. Patients without SDOH scores (e.g., reside outside of California; n=88 cases) were excluded. We used χ 2 -square and Wilcoxon-Mann Whitney tests to investigate for associations between SDOH factors (non-parametric, independent variables dichotomized as below vs above the median) and cardinal GI symptoms (continuous unweighted PRO-2 symptomatic severity and dichotomized clinical remission/active disease), patient-, and disease-related factors. In adults with UC in endoscopic or endo-histologic remission, we used univariate logistic regression to assess the risk of health disadvantage (SDOH score below median) and the presence of GI symptoms. RESULTS: Of the 166 UC cases, 46% (76/166), 38% (63/166), and 30% (49/166) were in clinical, endoscopic, and endo-histologic remission, respectively. Approximately one-fifth of cases (21%, 35/166) had SDOH scores below the state median. However, health disadvantage (below SDOH index median) was not associated with clinical, endoscopic, or endo-histologic disease activity; and neither were IBD duration; gender or race/ethnicity (all p>0.05) (Tab 1 ). Approximately one-third of cases had active GI symptoms despite endoscopic (32%, 20/63) and endo-histologic remission (29%, 14/49). However, none of the eight investigated SDOH domains were associated with increased risks for GI symptoms when UC had objective mucosal healing on colonoscopy (Tab 2 ) CONCLUSION: Although one-third of adults with mucosal healing of UC report GI symptoms (diarrhea/rectal bleeding), there was no association with multiple social determinants of health factors (e.g., education, neighborhood, economic, social, and environmental) in this secondary analysis of a prospective cohort.